TUTORING MODELS IN ARTIFICIAL INTELLIGENCE AND KNOWLEDGE SKILLS IN THE CONTEXT OF INDUSTRY 5.0 - Galvão, Frederico Ribeiro; Brandão, Heloanny de Freitas; Favaretto, José Eduardo Ricciardi (Seven Editora, 2026)
The expansion of generative artificial intelligence has increased the presence of digital tutoring systems in educational and corporate environments, enhancing the capacity for personalization, scalability, and availability of learning support. At the same time, Industry 5.0 repositions human beings at the center of technological transformation, reinforcing the relevance of knowledge skills for continuous learning, adaptability, and value creation. This article analyzes how artificial intelligence tutoring models relate to the development of knowledge skills in the context of Industry 5.0. The study adopts a theoretical conceptual approach, developed through an integrative literature review based on the authors’ doctoral qualification texts and the project’s authorized sources. The findings indicate that human, artificial, and hybrid tutoring models produce distinct effects on autonomy, motivation, engagement, self-regulated learning, and the development of cognitive, digital, and adaptive competencies. It concludes that AI-based tutoring can serve as a support infrastructure for the development of knowledge skills, provided it operates within a human-centered logic, articulated with pedagogical principles, human curation, knowledge-creation, and circulation processes.